2021
DOI: 10.21203/rs.3.rs-525693/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Coronavirus 2019 Disease Control Measures on the Incidence of Respiratory Infectious Disease and Air Pollutant Concentrations in Yangtze River Delta Region, China

Abstract: To investigate the changes of the respiratory infectious diseases (RID) and air quality during the COVID-19 outbreak over Yangtze River Delta Region, China. We investigate the impact of COVID-19 control measures on changes of RID and air quality by constructing two proportional test and fitting ARIMA and piecewise regression models. A total of 81,345 and 1,048,511 cases of RID were identified in Shanghai and Zhejiang Province, respectively. The incidence of seven RID and influenza decreased by 37.80% and 49.57… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…4 Moreover, several studies reported that strict precautionary measures for control of COVID-19 epidemic including lockdowns, homestays, school closures, wearing masks, and washing hands frequently might result in changes of an epidemic of infectious disease including respiratory infectious disease, digestive tract and animal-borne diseases, and so forth. 13,14 Therefore, it is necessary to understand the latest epidemiological characteristics of infectious diseases in China to provide a reference for summarizing the effects of past measures and formulating targeted measures in the future. 15 Through the system, hospitals, and clinics from all 31 provinces in the Chinese mainland could report confirmed cases of infectious disease directly to the county and national Center for Disease Control and Prevention (CDC), allowing real-time information to be delivered to a central database.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Moreover, several studies reported that strict precautionary measures for control of COVID-19 epidemic including lockdowns, homestays, school closures, wearing masks, and washing hands frequently might result in changes of an epidemic of infectious disease including respiratory infectious disease, digestive tract and animal-borne diseases, and so forth. 13,14 Therefore, it is necessary to understand the latest epidemiological characteristics of infectious diseases in China to provide a reference for summarizing the effects of past measures and formulating targeted measures in the future. 15 Through the system, hospitals, and clinics from all 31 provinces in the Chinese mainland could report confirmed cases of infectious disease directly to the county and national Center for Disease Control and Prevention (CDC), allowing real-time information to be delivered to a central database.…”
Section: Introductionmentioning
confidence: 99%
“…State Council of the People's Republic of China revised the Law of the People's Republic of China on prevention and control of infectious diseases in 2013 and 2020 4 . Moreover, several studies reported that strict precautionary measures for control of COVID‐19 epidemic including lockdowns, homestays, school closures, wearing masks, and washing hands frequently might result in changes of an epidemic of infectious disease including respiratory infectious disease, digestive tract and animal‐borne diseases, and so forth 13,14 . Therefore, it is necessary to understand the latest epidemiological characteristics of infectious diseases in China to provide a reference for summarizing the effects of past measures and formulating targeted measures in the future.…”
Section: Introductionmentioning
confidence: 99%